Interest and learning motivation with student participation - Muhamad Uyun; Yuli Bahriah; Fitriani Fitriani (Psikoislamedia : Jurnal Psikologi, 2022)
Many factors affect student participation in the learning process. According to the researcher, two (2) most dominant factors are interest and learning motivation. For that, researchers are interested in proving it empirically. This research aimed to determine the correlation between interest and motivation to learn with student participation. The analysis technique to test the hypothesis by using multiple regression. The data analysis results proved a significant positive relationship between interest and motivation to learn with student participation (r=0.521 :( p<0.01). There was a significant positive relationship between interest and student participation (r=0.516;(<0.01) , and there is a significant positive relationship between learning motivation and student participation (r=0.520; ( p<0.01). Furthermore, the variable of learning motivation is a variable that has a more significant influence on student participation which can be seen from the B value of 0.679 while the interest variable is 0.178.